2003
DOI: 10.1038/ncb1077
|View full text |Cite|
|
Sign up to set email alerts
|

Polycomb CBX7 has a unifying role in cellular lifespan

Abstract: In contrast to cancer cells and embryonic stem cells, the lifespan of primary human cells is finite. After a defined number of population doublings, cells enter in an irreversible growth-arrested state termed replicative senescence. Mutations of genes involved in immortalization can contribute to cancer. In a genetic screen for cDNAs bypassing replicative senescence of normal human prostate epithelial cells (HPrEC), we identified CBX7, a gene that encodes a Polycomb protein, as shown by sequence homology, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
306
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(319 citation statements)
references
References 29 publications
10
306
3
Order By: Relevance
“…In normal human diploid fibroblast WI-38 cells, NUAK1 is suggested to regulate senescence by a mechanism that does not involve p53 (Humbert et al, 2010), which is not consistent with our findings for p53 and p21/WAF1 in A549 or G361 cells and also conflicts with earlier reports that have suggested that the p53 pathway is involved in regulation of senescence in normal human cells (Gil et al, 2004;Herbig et al, 2004). Results from Humbert et al (2010) also have shown that, depending on the cell type, the aneuploidy induced by NUAK1 might have different consequences: senescence or cell death.…”
Section: Lkb1/nuak1 Directly Regulates P53contrasting
confidence: 99%
“…In normal human diploid fibroblast WI-38 cells, NUAK1 is suggested to regulate senescence by a mechanism that does not involve p53 (Humbert et al, 2010), which is not consistent with our findings for p53 and p21/WAF1 in A549 or G361 cells and also conflicts with earlier reports that have suggested that the p53 pathway is involved in regulation of senescence in normal human cells (Gil et al, 2004;Herbig et al, 2004). Results from Humbert et al (2010) also have shown that, depending on the cell type, the aneuploidy induced by NUAK1 might have different consequences: senescence or cell death.…”
Section: Lkb1/nuak1 Directly Regulates P53contrasting
confidence: 99%
“…Much less is known about how the function and expression of the PRCs and their components are controlled. The regulation of CBX7 is particularly interesting because CBX7 is implicated in senescence (Gil et al ., 2004) and cancer (Bernard et al ., 2005; Scott et al ., 2007; Pallante et al ., 2008; Karamitopoulou et al ., 2010). In addition, CBX7 levels and consequently the composition of PRC1 complexes change dramatically during ES cell differentiation (Morey et al ., 2012; O'Loghlen et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a component of PRC1, CBX7 represses the INK4/ARF locus (Gil & O'Loghlen, 2014). Indeed, CBX7 was first identified in a screen for bypass of replicative senescence (Gil et al ., 2004). More recently, CBX7 was recognized as the main orthologue of Drosophila Polycomb implicated in maintaining the self‐renewal of embryonic stem (ES) cells (Morey et al ., 2012; O'Loghlen et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The pRB pathway is also activated by upregulation of p16INK4a. The mechanism by which expression of p16INK4a is increased is not known, although it is likely to involve regulation of polycomb proteins that repress expression of p16INK4a (11,47,62).…”
Section: Senescence Inducing Pathwaysmentioning
confidence: 99%